2017
DOI: 10.1098/rsos.171040
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of owner-directed aggressive behavioural tendencies of dogs in situations of possession and manipulation

Abstract: Excessive aggression is a common behaviour problem in dogs that can have various destructive effects on the affected people and the implicated dog. Aggressive behaviour directed towards the owner or other family members is one of the most frequently occurring aggressive phenotypes. Here, we examine the reliability of a short questionnaire assessing aggressive behaviours by two, contextually different behavioural tests: ‘take away bone’ and ‘roll over’. Based on dogs' behaviour in the tests, we sorted dogs (N =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 42 publications
(78 reference statements)
0
10
1
Order By: Relevance
“…Finally, an observational study on n = 93 Hungarian dogs that measured both obedience and owner-directed aggression found that males and intact dogs tended to be less obedient than females and gonadectomized dogs, but that gonadectomized dogs that were less obedient were also more likely to show signs of owner-directed aggression [229].…”
Section: Boldness-related and Aggressive Behaviormentioning
confidence: 98%
“…Finally, an observational study on n = 93 Hungarian dogs that measured both obedience and owner-directed aggression found that males and intact dogs tended to be less obedient than females and gonadectomized dogs, but that gonadectomized dogs that were less obedient were also more likely to show signs of owner-directed aggression [229].…”
Section: Boldness-related and Aggressive Behaviormentioning
confidence: 98%
“…The owners were first asked to fill out a questionnaire consisting of 20 items about their dogs’ obedience and aggressive tendencies [ 40 ]. They had to mark their answers on a 10-point Likert scale ( Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…As consecutive tests of potentially aggressive responses might increase the animal’s aggression [ 40 , 41 ], there was a 2–3 min break between these two tests to minimize the risk of this effect.…”
Section: Methodsmentioning
confidence: 99%
“…Controversies have arisen about whether the assessments conducted in animal shelters do indeed predict future household behaviours after adoption [ 21 , 22 , 23 ]. One argument is that certain behaviours, such as aggression [ 24 ] and separation anxiety [ 25 ], are context- and stimulus-specific. Since the behavioural assessment is usually done by an examiner who may be perceived as unfamiliar and intimidating to the dog, the result may not be transferable to a situation where an owner interacts with the dog [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…One argument is that certain behaviours, such as aggression [ 24 ] and separation anxiety [ 25 ], are context- and stimulus-specific. Since the behavioural assessment is usually done by an examiner who may be perceived as unfamiliar and intimidating to the dog, the result may not be transferable to a situation where an owner interacts with the dog [ 23 , 24 ]. Although such arguments have been raised, behavioural assessments still reliably describe animals’ behaviours within the shelter [ 19 , 26 ].…”
Section: Introductionmentioning
confidence: 99%